2018
DOI: 10.1080/03004279.2018.1515969
|View full text |Cite
|
Sign up to set email alerts
|

Using different art forms to investigate the impact on children’s involvement in literacy activities

Abstract: Using different art forms to investigate the impact on children's involvement in literacy activities Much of the research into factors that affect children's school performance has focused on parental involvement rather than the nature of children's activities undertaken in school. More research is therefore needed to examine the kinds of activities that affect performance and, in particular, whether the degree of involvement children experience in those activities can affect school performance. Children in fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…For example, digital tools and toys (Sakr & Scollan, 2019;Leung et al, 2020;Peppler et al, 2019;Li et al, 2021;Abdi & Cavus, 2019, Duncan et al, 2020Kewalramani et al, 2021;Kewalramani et al, 2020;Vogt & Hollenstein, 2021;Alemi & Haeri, 2020;Bers, 2021) even educational apps and games (Vanbecelaere et al, 2020;Adbo & Carulla, 2020;Williams & Thevenow, 2021;Ramani et al, 2020;Subaramaniam & Mon, 2020;Disney et al, 2019;Outhwaite et al, 2019). What is interesting in this data is that learning through play educational programme in many dimensions have been developed (Gibb et al, 2021;Parrott & Cohen, 2021;Theodotou, 2019). We found that very few study examined on dimension of learning through play.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, digital tools and toys (Sakr & Scollan, 2019;Leung et al, 2020;Peppler et al, 2019;Li et al, 2021;Abdi & Cavus, 2019, Duncan et al, 2020Kewalramani et al, 2021;Kewalramani et al, 2020;Vogt & Hollenstein, 2021;Alemi & Haeri, 2020;Bers, 2021) even educational apps and games (Vanbecelaere et al, 2020;Adbo & Carulla, 2020;Williams & Thevenow, 2021;Ramani et al, 2020;Subaramaniam & Mon, 2020;Disney et al, 2019;Outhwaite et al, 2019). What is interesting in this data is that learning through play educational programme in many dimensions have been developed (Gibb et al, 2021;Parrott & Cohen, 2021;Theodotou, 2019). We found that very few study examined on dimension of learning through play.…”
Section: Discussionmentioning
confidence: 88%
“…An early study by Theodotou (2019) showed the positive contribution of PLA to children's literacy development. With the same objective, Colliver et al (2021) conducted numerical experiments on pre-schoolers' exposure to parents and educators.…”
Section: Language (12 Articles)mentioning
confidence: 99%
See 1 more Smart Citation
“…Following that publication, PLA has also been used in small-scale studies to support children's literacy, social and personal skills (Theodotou, 2019(Theodotou, , 2017b. Recently, it was also used in a bigger research project to measure children's involvement comparing different art forms over a control group (Theodotou, 2018).…”
Section: The 'Play and Learn Through The Arts' (Pla) Programmementioning
confidence: 99%
“…Μέσω της παρούσας ενότητας ασφαλώς και δεν εξαντλούνται τα παραδείγματα προγραμμάτων στα οποία αναδεικνύεται η αξία της τέχνης στην εκπαίδευση. Επιγραμματικά θα αναφερθεί η συνεργασία της Maxine Greene με το Lincoln Center Institute, με προσανατολισμό ένα «οπτικό» πρόγραμμα σπουδών μέσω της συνεργασίας με καλλιτέχνες (Davis, 2008), οι εκπαιδευτικές μεταρρυθμίσεις του «Καλλιτεχνικού προγράμματος σπουδών» σε Αγγλία, Ουαλία, όπως και σε Σιγκαπούρη και Νέα Ζηλανδία (Albers & Murphy, 2000), η «Καμπάνια για τη ζωγραφική» (The campaign for drawing) στη Μ. Βρετανία το 2000 (Γραφάκου & Λαμπίτση, 2011), ενώ ένα πρόγραμμα το οποίο βρίσκεται σε εξέλιξη τα τελευταία χρόνια είναι το "Play and Learn through the Arts (PLA)" (Παιχνίδι και μάθηση μέσω των τεχνών), για παιδιά πέντε και έξι ετών, το οποίο αποτελεί μια διαθεματική προσέγγιση υποστήριξης του γραμματισμού ως κοινωνικής πρακτικής σε ένα φιλελεύθερο, παιδοκεντρικό περιβάλλον (Theodotou, 2017(Theodotou, , 2018(Theodotou, , 2019.…”
Section: τα αναγνωστικά μονοπάτιαunclassified